Решите неравенство (x-4)/(x^2-5x+6> =(x+2)/(-x^2-x+12)

Кристинаuy Кристинаuy    1   28.07.2019 01:10    0

Ответы
kcufka123456789 kcufka123456789  25.09.2020 15:23
(x-4)/(x²-5x+6)+(x+2)/(x²+x-12)≥0
x²-5x+6=0
x1+x2=5 U x1*x2=6⇒x1=2 U x2=3
x²+x-12=0
x1+x2=-1 U x1*x2=-12⇒x1=-4 U x2=3
(x-4)/[(x-2)(x-3)]+(x+2)/[(x+4)(x-3)]≥0
(x²-16+x²-4)/[(x-2)(x-3)(x+4)]≥0
(2x²-20)/[(x-2)(x-3)(x+4)]≥0
2(x-√10)(x+√10)/[(x-2)(x-3)(x+4)]≥0
x=√10 x=-√10 x=2  x=3  x=-4
               _                +              _              +              _            +
(-4)[-√10](2)(3)[√10]
 x∈(-4;-√10] U (2;3) U [√10;∞)
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра